A baboon model for endometriosis: implications for fertility - Fazleabas Asgerally T; Hastings Julie M (BMC, 2006)
Abstract Endometriosis is one of the most common causes of chronic pelvic pain and infertility in women in the reproductive age group. Although the existence of this disease has been known for over 100 years our current knowledge of its pathogenesis and the pathophysiology of its related infertility remains unclear. Several reasons contribute to our lack of knowledge, the most critical being the difficulty in carrying out objective long-term studies in women. Thus, we and others have developed a model of this disease in the non-human primate, the baboon (Papio anubis). Intraperitoneal inoculation of autologous menstrual endometrium results in the development of endometriotic lesions with gross morphological characteristics similar to those seen in the human. Multiple factors have been implicated in endometriosis-associated infertility. We have described aberrant levels of factors involved in multiple pathways important in the establishment of pregnancy, in the endometrium of baboons induced with endometriosis. Specifically, we have observed dysregulation of proteins involved in invasion, angiogenesis, methylation, cell growth, immunomodulation, and steroid hormone action. These data suggest that, in an induced model of endometriosis in the baboon, an increased angiogenic capacity, decreased apoptotic potential, progesterone resistance, estrogen hyper-responsiveness, and an inability to respond appropriately to embryonic signals contribute to the reduced fecundity associated with this disease.